AKTIVITAS ANTIBAKTERI DAN SITOTOKSISITAS EKSTRAK DAUN KEDONDONG HUTAN - Asnani Asnani; Winiati P. Rahayu; Betty Sri Laksmi Jenie; Nancy D. Yuliana (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2017)
Wild mango (Spondias pinnata) leaves is a very popular herb in Southeast Sulawesi, has been used as herbal medicine at Southern and Southeastern Asia. The purpose of this study was to determine the antibacterial activity, cytotoxicity and phytochemical contents of wild mango (Spondias pinnata) leaves extracts. The extraction was performed using a combination of maceration with ethanol and ultra-sonication. The antibacterial activity assay of the extracts was examined against Staphylococcus aureus, Listeria monocytogenes, Klebsiella pneumoniae, Morga-nella morganii, Pseudomonas aeruginosa, Shigella sonnei, Escherichia coli, and Salmonella Typhi. The cytotoxicity test was performed on Vero cells using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The extracts were able to inhibit all tested bacteria with inhibition zone ranging from 4.48 to 7.49 mm. P. aeruginosa was the most susceptible bacterium, producing inhibition zone of 7.49 mm and a MIC (minimum inhibition concentration) value of 6.25 mg/mL. The extract was not toxic to Vero cells as indicated by IC50 (inhibitory concentration of 50%) values at 347 µg/mL, or more than the toxicity limit of 50 µg/mL. Phytochemical analysis of the extract revealed that it contained steroids, tannins, and saponins. The flavonoids concentration was 23.2±0.33 mg/g and while the phenolic substance was 43.2±0.45 mg/g. The FTIR analysis showed O-H, C-H, X=C=Y, C=O, C=C, and C-O-C as the functional groups in the extracts. This result suggests that the ethanol extract of S. pinnata leaves has the potential to be used as natural preservatives in foods.